ANALISIS SEMIOTIKA CHARLES SANDERS PEIRCE PADA SIMBOL RAMBU LALU LINTAS DEAD END - Aryani, Saleha; Yuwita, Mia Rahmawati (Mahadaya: Jurnal Bahasa, Sastra, Dan Budaya, 2023)
This research is entitled Semiotic Analysis of Dead End Traffic Sign Symbols. This study aims to determine the semiotic meaning of the traffic symbol Dead End based on the meaning of color, shape and also the meaning represented by the word Dead End itself using Charles Sanders Peirce’s theory. The method used in this study is a qualitative descriptive method because as a whole it explains how the process of sign formation and the meaning of the sign is carried out through a semantic approach. The results of this study indicate that the color, shape and also the naming of a symbol are things that have been determined and produced from every human perspective based on reality. Based on this research, it can be concluded that every symbol that is formed based on color, shape and also a word has a meaning according to each person's perspective. Keywords: Semiotics, Semantics, Symbol, Dead End